Community groups, organisations, and employers respond to the challenges of the Covid-19 pandemic: A story of resilience and continued vulnerability - Katharine Abba; Adele Ring; Peter Lloyd; Rachel Anderson de Cuevas; Shaima Hassan; Mark Goodall; Pam Clarke; Kerry Hanna; Saiqa Ahmed; Gerry Allen; Neil Joseph; Alan Price; et al. (BMC Public Health)
Abstract Background The Covid-19 pandemic profoundly disrupted societal systems, prompting community groups, voluntary organizations and employers to adapt rapidly to emerging needs. Here we present findings of a study conducted in the North West of England, exploring how groups and organisations adapted and responded to local needs at this time. Methods We conducted semi-structured interviews with ‘key informants’ within local community voluntary, charity, faith or social enterprise (VCFSE) sector groups and organisations (n = 19) and large/ medium employers within any sector (n = 6). Interview transcripts were analysed thematically by a team of academic researchers and ‘Public Advisers’ with knowledge of local communities. Findings Our findings reveal that community-based VCFSE groups and organisations played a critical role in addressing immediate needs such as food insecurity, isolation, and health vulnerabilities. This response was motivated by a strong sense of responsibility for the wellbeing of the clients and communities they served, and was enabled by their strong community networks, local knowledge, and ability to increase system capacity through collaboration. However, in a context of increased wellbeing needs later in the pandemic, many struggled to restart their core business, constrained by depleted resources and difficulties in interpreting and applying government ‘Covid-secure’ legislation and guidance. Conclusion The study underscores the importance of local resilience, highlighting the VCFSE sector’s central role in addressing inequalities exacerbated by crises. It calls for substantial long-term investment to sustain this vital infrastructure, which is critical not only for recovery but also for preparedness for future societal shocks.